Phosphodiesterase type 5 inhibitors use and risk of colorectal cancer: a systematic review and meta-analysis - Bhagavathula, Akshaya Srikanth; Tesfaye, Wubshet; Vidyasagar, Kota (International journal of colorectal disease, 2021)
BACKGROUND: Experimental evidence has revealed that phosphodiesterase five inhibitors (PDE5is) increase epithelial barrier function and suppress intestinal carcinogenesis. Few epidemiological studies have investigated the role of PDE5i in increasing the risk of colorectal cancer (CRC); however, these studies have proffered varying conclusions. We therefore aimed to perform a comprehensive review and meta-analysis to investigate whether PDE5i use is associated with the incidence of CRC. METHODS: Databases, namely, PubMed, Scopus, Embase, and Web of Science, were used for literature search. Observational studies (published until January 31, 2021) that assessed the association of PDE5i use with CRC incidence were considered. Pooled relative risk (RR) estimates and corresponding 95% confidence intervals (CIs) were calculated using the DerSimonian-Laird random-effects model. RESULTS: We identified four retrospective studies that involved 965,044 participants and 3,518 CRC cases detected during a mean follow-up of 12.7 years. Pooled results indicated a significantly reduced CRC risk among all PDE5i users (RR, 0.85; 95% CI, 0.76-0.95; P = 0.004, I2 = 63%). Moreover, continuous use of PDE5i was associated with a significantly reduced risk of CRC (RR, 0.63; 95% CI, 0.59-0.68; P < 0.001, I2 = 0.0%). However, the type of PDE5i exhibited no association with the risk of CRC (RR, 1.00; 95% CI, 0.98-1.02; I2 = 84.7%). CONCLUSION: Our findings suggest that continuous use of PDE5i was associated with a significantly reduced risk of CRC development. Future studies with a longitudinal design and adequate control of confounding factors are required to clarify whether a longer duration of PDE5i use alters the risk of CRC.
Keywords: Pharmacoepidemiology; Sildenafil; Colorectal Neoplasms; retrospektivní studie; inhibitory fosfodiesterasy 5; Phosphodiesterase five inhibitors; Meta-analysis; Humans; Risk; kolorektální nádory; lidé; riziko; Retrospective Studies; Colorectal cancer; Phosphodiesterase 5 Inhibitors; incidence; Incidence